Effect of Hyperbaric Oxygen Therapy on Enhancing Fertility (Literature Review) - Hisnindarsyah; Wahyudi , Ahyar (Jurnal Multidisiplin Madani, 2023)
Ovulatory disorders, damage to the fallopian tubes, uterine issues, and conditions such as endometriosis have been identified as primary causes of female infertility. This article aims to explore the potential of hyperbaric oxygen therapy in enhancing fertility. Hyperbaric Oxygen Therapy (HBOT) is a medical procedure that involves inhaling pure oxygen (100%) within a chamber or room under pressure higher than normal atmospheric pressure, specifically over 1 absolute atmosphere (ATA), to accelerate and enhance the body's healing and recovery abilities. Under elevated atmospheric pressure, gaseous oxygen can dissolve more readily into the blood plasma. Research results suggest that HBOT holds potential in improving fertility due to endometrial receptivity issues and may also boost male fertility. Future studies need to be conducted on the impact, safety, and mechanisms of HBOT in relation to enhancing female fertility